The presence of Gea heptagon (Hentz) and new records of Argiope genus from Argentina with the description of a new species (Araneae, Araneidae) - Rodriguez Artigas, Sandra Mónica (2015)
Argiope is represented in Argentina by three species (A. argentata (Fabricius), A. trifasciata (Forsskål) and A. ericae Levi); while the presence of Gea heptagon (Hentz) was suggested as probable in the northern of Argentina, until present no record was provided to our country. In this paper, we describe and illustrated a new species of Argiope, Argiope kaingang nov. sp. (female only) collected in Mercedes, Corrientes Province. New records of A. argentata, A. trifasciata, and the first record of G. heptagon are also provided to the north of Argentina.